Ending hepatitis C in the United States: the role of screening - Coffin PO (Dove Medical Press, 2014)
Phillip O Coffin,1 Andrew Reynolds21San Francisco Department of Public Health, Substance Use Research Unit, San Francisco, CA, USA; 2Project Inform, San Francisco, CA, USAAbstract: The US faces at least two distinct epidemics of hepatitis C virus infection (HCV), and due largely to revised screening recommendations and novel therapeutic agents, corresponding opportunities. As only 49%–75% of HCV-infected persons in the US are aware of their infection, any chance of addressing HCV in the US is dependent upon screening to identify undiagnosed infections. Most HCV in the US consists of longstanding infections among persons born during 1945–1965 who are suffering escalating rates of liver-related morbidity and mortality. Mathematical modeling supports aggressive action to reach and treat these persons to minimize the subsequent burden of advanced liver disease on patients and the health care system. Incident infection is primarily among persons who inject drugs, less than 10% of whom have been treated for HCV. Expanded screening and treatment of active persons who inject drugs raises the prospect of utilizing "treatment as prevention" to stem the tide of incident HCV infections in this population. HIV-positive men who have sex with men (MSM) represent a population at risk for sexually transmitted HCV who may also benefit from adjusted screening guidelines to identify both acute and chronic infections. Prisoners also represent a critical population for aggressive screening and treatment. Finally, the two-stage testing algorithm for HCV diagnosis is problematic and difficult for patients and providers to navigate. While emerging therapeutics raise the prospect of reducing HCV-related morbidity and mortality, as well as eliminating new infections, major barriers remain with regard to identifying infections, improving access to treatment, and ensuring payer coverage of costly new therapeutic regimens.Keywords: HCV screening, HCV treatment, treatment as prevention